Analisis Proses Keputusan Pembelian Konsumen Teh di Kedai Dekat Tea - Divanisha, Azka; Budiman, Muhammad Arief (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Dekat Tea is a tea shop in Bandung offering a variety of quality teas. Despite the growing trend of tea consumption and limited competition in the city, Dekat Tea faces significant fluctuations in monthly income. This study aims to explore the consumer purchasing decision-making process and its characteristics, using a descriptive qualitative approach through in-depth interviews with 50 consumers. The results show that the majority of consumers are women aged 17–25 with high school/vocational school and undergraduate degrees, and are from the middle class. The purchasing decision process is influenced by internal (health benefits) and external (social media) factors, with TikTok as the primary source of information. During the evaluation stage, consumers tend to consider product aspects, location, and price. Purchase decisions are generally driven by the product selection offered by Dekat Tea, its strategic location, and trust in the brand. Most consumers are satisfied and willing to make repeat purchases or provide recommendations. These findings suggest the importance of optimizing social media, especially TikTok, as a promotional medium, innovating product variants according to young consumers' preferences, and diversifying sales channels to increase brand visibility and maintain revenue stability.